1998
DOI: 10.1002/(sici)1097-0142(19980315)82:6<1013::aid-cncr2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The role of the HLA-DQA1 gene in resistance to atrophic gastritis and gastric adenocarcinoma induced byHelicobacter pylori infection

Abstract: RESULTS. Of 70 -90% of patients with gastric adenocarcinoma. The epidemiologic features of gastric adenocarcinoma and H. pylori infection are similar,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
5
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 28 publications
3
67
5
3
Order By: Relevance
“…They found that the allele frequency of DQA1 was significantly lower in H. pylori positive atrophic gastritis group than in H. pylori positive superficial gastritis and normal control groups. In addition, the al lele frequency of DQA1 also was significantly lower in H. pylori positive intestinal type gastric adenocarcinoma group than in normal control, H. pylori positive superficial gastritis, and diffuse type gastric adenocarcinoma groups [69] . The importance of host genetic factors in determining the outcome of H. pylori infection was further demonstrated by Sakagami and colleagues.…”
Section: Host Genetic Factorsmentioning
confidence: 81%
“…They found that the allele frequency of DQA1 was significantly lower in H. pylori positive atrophic gastritis group than in H. pylori positive superficial gastritis and normal control groups. In addition, the al lele frequency of DQA1 also was significantly lower in H. pylori positive intestinal type gastric adenocarcinoma group than in normal control, H. pylori positive superficial gastritis, and diffuse type gastric adenocarcinoma groups [69] . The importance of host genetic factors in determining the outcome of H. pylori infection was further demonstrated by Sakagami and colleagues.…”
Section: Host Genetic Factorsmentioning
confidence: 81%
“…26 Absence of HLA-DQA1 0101 may be a host genetic risk factor for H. pylori-associated atrophic gastritis and for intestinal-type gastric adenocarcinoma. 27 Lewis antigen and secreted phenotype have been related to the attachment of H. pylori to gastric mucosa and subsequent epithelial damage. 28 It has been reported that anomalous Lewis antigen (a) expression in Lewis (a-bϩ) phenotype individuals was closely related to the severity of the histologic lesions, especially to dysplasia and type III intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…At the expected false significance rate of 0.88%, 54 up-regulated and 471 down-regulated genes were detected in colon polyps compared to normal mucosa crypts. gastritis and gastric cancer (33), although the pathobiological role in colon carcinogenesis is not clear.…”
Section: Fcgbp Slc26a2 Eplin Tspan1 Pdcd4 Pex1 Mtus1 Fabp1 Ddmentioning
confidence: 99%